The Stylistic Characteristics of Wooden Carts - Chaolumen; D. Sereeterdorj; M. Molomjamts (International Journal of Social Sciences and Public Administration, 2025)
Wooden carts, as a traditional folk art form with a long history and rich cultural significance, possess unique stylistic features and artistic charm that merit in-depth research and discussion. This paper conducts a comprehensive analysis from multiple perspectives, including the imagery, artistic characteristics, and cultural connotations of wooden carts, to reveal the aesthetic value and symbolic meaning of their design. The study finds that the form, color application, decorative patterns, and material selection of wooden carts all reflect distinct ethnic styles and regional characteristics. Beyond their unique artistic appeal, wooden carts embody profound symbolic meanings and cultural significance, serving as important carriers of ethnic cultural heritage. Furthermore, wooden carts hold broad application prospects in modern design, offering fresh inspiration and vitality to product design, architectural design, and artistic creation. The paper also examines the challenges in the preservation and transmission of wooden carts and proposes corresponding countermeasures, aiming to provide insights for the protection and development of this intangible cultural heritage.